Motivasi Belajar Warga Belajar Program Kejar Paket B di PKBM Maju Jaya Kecamatan Bangkinang Kota - Elsa Marel; Daeng Ayub Natuna; Said Suhil Achmad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims to determine the motivation of citizens to learn Packet B program in the PKBM Maju Jaya. The problems in this study is the high motivation of citizens to learn How Packet B program in PKBM Maju Jaya The benefits of research to increase knowledge on matters related to motivation, motivation to learn, Citizens Learning, especially for researchers. This research will benefit all citizens of learning. This is a descriptive study with a quantitative approach that aims to describe the results of research by the numbers. The sampling technique using sampling techniques saturated. This technique is used because the population is relatively small, and all the members of the study population sampled. Data collection techniques in this research is to use the questionnaire as a method of data collection, totaling 35 items statement. After the questionnaire in the trial, there are three items that are not valid. Data obtained from respondents of 20 people to sample the test and 37 people with Cronbach's alpha = 0.978 Based on the recapitulation percentage Citizens Learning about Learning Motivation Packet B program in the CLC Maju Jaya subdistrict Bangkinang otivasi City Extrinsic more dominant than intrinsic motivation.Keywords: Motivation, motivation to learn, Citizens Learning.